(untitled) (Asian Journal of Social Science Studies, 2024)
Clinical practice is a necessary learning stage of medical students and an important supplement to classroom learning. Endocrine diseases have a high incidence and involve a wide range of people, and the importance of endocrinology in clinical practice cannot be ignored. At present, there are some problems in the process of internship, such as students’ insufficient attention, the effect of traditional teaching is not satisfactory, lack of humanistic quality education of students, the evaluation mechanism lack or not perfect, etc. To solve these problems, teachers in endocrinology department can improve the teaching effect of endocrinology practice by adjusting students’ attitude, adopting scientific teaching methods, strengthening the humanistic quality education and improving the assessment system.